2015
DOI: 10.1177/1054137315608347
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Socioeconomic Status and the Health of Older People in the United Kingdom

Abstract: Correlates of socioeconomic status and the health of older people in the United Kingdom: a review. Illness, Crisis & Loss, 24 (4). pp. 195-216.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Similarly, our study found that people with higher income levels had better adaptation. It is stated that there is a relationship between socioeconomic status and worse health, chronic diseases, mortality, worse functional capacity, sleep disturbances and have a shorter life expectancy in the elder 31,32 . However, it is reported that the increase in income status has a positive effect on physical and mental health, life satisfaction, quality of life and subjective well-being 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our study found that people with higher income levels had better adaptation. It is stated that there is a relationship between socioeconomic status and worse health, chronic diseases, mortality, worse functional capacity, sleep disturbances and have a shorter life expectancy in the elder 31,32 . However, it is reported that the increase in income status has a positive effect on physical and mental health, life satisfaction, quality of life and subjective well-being 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic status (SES) differentials in health are well established in western developed countries. Individuals with lower SES are more likely to experience numerous health problems and higher rates of mortality compared to those of higher SES (Rahman, Khan, & Hafford-Letchfield, 2015;Marmot & Wilkinson, 2001;Pappas, Queen, Hadden, & Fisher , 1993;Williams, 1990). This so-called 'SES-health gradient' has been observed in many studies of people from different age groups across a wide range of SES determinants, health indicators and methodologies (Smith, 1999;Goldman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous findings, demographic variables were chosen to include in the modelling to control for the effects of known determinants of health and wellbeing. Demographic variables included highest level of education, measures of economic status (in the form of income and home ownership) and age, all of which have a good evidence base as predictors of health (Martikainen et al 2008;Marmot et al 2012;Rahman et al 2016;Foster et al 2018). Education was dichotomised as up to school level or above school level to simplify regressions.…”
Section: Rationale For Independent Variablesmentioning
confidence: 99%